Cryptic Diversity of Barred Mudskippers, Periophthalmus argentilineatus (Valenciennes, 1837), from the Southern Coast of Java and East Lombok, Indonesia inferred by COI Mitochondrial Gene - Arisuryanti, Tuty; Aji, Katon Waskito; Herawati, Happy; Sari, Indah Paramita; Rha’ifa, Febrina Amaliya; Febriyanti, Diana; Priyono, Dwi Sendi (Universitas Gadjah Mada, 2024)
The Barred Mudskipper (P. argentilineatus) is an amphibious fish species that displays fully terrestrial behaviour during low tides. Previous studies have indicated the existence of cryptic species of the barred mudskipper, leading to difficulties in taxonomic identification due to similarities in morphological characteristics. Therefore, this study aimed to generate DNA barcodes for Indonesian barred mudskipper populations. We collected ten specimens from Clungup Beach and Kondang Bandung Beach, representing our samples. Additionally, we incorporated 25 previously collected COI sequences from Indonesia into our analysis. The mitochondrial COI gene was amplified using PCR and analysed using various bioinformatics programs. This study provides evidence for the presence of three genetically distinct clades (A, B, and C) within the P. argentilineatus population in Indonesia, with a deep genetic divergence of 2.41% to 6.12%. Clade A showed a high genetic divergence of 5.51-6.12%, suggesting the presence of a cryptic species consistent with previous studies. The high level of haplotype diversity and low nucleotide diversity observed in each clade suggest a population bottleneck followed by a rapid expansion. The lack of geographical separation in the haplotype network analysis indicates that gene flow between populations may have been facilitated by glaciation events in the past. These findings contribute to a better understanding of the biodiversity of the barred mudskipper species in Indonesia and will aid in the accurate identification of cryptic species. This study highlights the importance of using molecular techniques to complement morphological identification in understanding the evolution and diversity of mudskipper fish species.